Government support of the garment and knitting industry within the scope of business activity - Maksudov, Abdusalam (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article talks about state support for the clothing and knitting industry in the country and about the peculiarities of the development of the industry.